PENGARUH TINGKAT SUKU BUNGA TERHADAP INVESTASI PENANAMAN MODAL DALAM NEGERI (PMDN) DI SUMATERA UTARA TAHUN 2015-2024 - Mardiah, Siti (EKOMBIS: JURNAL FAKULTAS EKONOMI, 2025)
This study aims to empirically examine the effect of interest rates on Domestic Investment (PMDN) in North Sumatra Province during the period 2015-2024. Using a quantitative approach and time series data for ten years, this study uses simple linear regression analysis to assess the strength and direction of the relationship between variables. The results showed that interest rates have a negative and significant effect on deposits.  The t-test results confirmed the significance of this relationship. This finding supports the economic theory that high interest rates will increase the cost of capital and inhibit investment expansion. This study highlights the importance of maintaining an optimal interest rate level as a strategic tool to foster sustainable regional investment growth.